2020
DOI: 10.1007/s40200-020-00632-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of angiotensin converting enzyme (I/D) polymorphism (rs4646994) and coronary heart disease among a male Iraqi population with type 2 diabetes mellitus

Abstract: Background Insertion deletion (I/D) polymorphism (rs4646994) in the angiotensin-converting enzyme (ACE) has a substantial effect on coronary heart disease (CHD). The amplification of an Alu repetitive element in an intron of the ACE has shown three potential genotypes of I/I and D/D as homozygous, and I/D as heterozygous.Objective The objective of this study was to investigate the association between the ACE gene polymorphism and CHD among male Iraqi patients with and without type2 diabetes mellitus (T2DM). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…24 Troponin I play an important roles in myocardial infarction as a specific biomarker. 4 These findings are consistent with Ammirati et al, (2021) 25 Cardiac special troponin (cTn) are significant Common biomarkers utilized in contemporary clinical Diagnosis to suspected MI, and their altitude is a key feature in the diagnosis of acute MI. 26 The causes of myocardial damage are many, and myocardiocyte apoptosis, with or without obvious indications of necrosis, may cause the release of cTn from injured cells.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…24 Troponin I play an important roles in myocardial infarction as a specific biomarker. 4 These findings are consistent with Ammirati et al, (2021) 25 Cardiac special troponin (cTn) are significant Common biomarkers utilized in contemporary clinical Diagnosis to suspected MI, and their altitude is a key feature in the diagnosis of acute MI. 26 The causes of myocardial damage are many, and myocardiocyte apoptosis, with or without obvious indications of necrosis, may cause the release of cTn from injured cells.…”
Section: Discussionsupporting
confidence: 84%
“…Chest discomfort that radiates to the left arm or side of the neck, shortness of breath, perspiration, nausea, vomiting, an irregular heartbeat, anxiety, exhaustion, and other symptoms are all signs of MI. 3,4 The term "silent MI" refers to the approximately 64% of MI patients do not experience chest discomfort. 5 MI is caused by a number of factors, including older age, cigarette use high concentration of cholesterol and fat levels, diabetes, obesity, inactivity, chronic renal disease, hypertension, high levels of bad cholesterol LDL (low density lipoprotein), excessive alcohol intake and use of cocaine and amphetamines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zmorzynski et al observed the association between Del/DEl genotype and more than 2-fold risk of multiple myeloma [ 34 ]. The Del/Del genotype was significantly more frequent in coronary heart disease (CHD) patients with type2 diabetes mellitus (T2DM) compared to each of CHD patients without T2DM and control populations [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…24 ACE is connected with some cardiovascular abnormalities such as myocardial infarction, 25 cardiovascular diseases, 26 strokes and coronary heart disease. 27 Some studies have evaluated the relationship between ACE I/D polymorphism and hypertension in North Indian, 28 Chinese, 29 and Brazilian population. 21 However, few studies have assessed the relationship between ACE and lipid profiles in the Saudi population that determine the ACE I/D genotypes with familial hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%